Myeloid-Derived Suppressor Cells in Lung Transplantation - Heigl, Tobias; Singh, Anurag; Saez-Gimenez, Berta; Kaes, Janne; Van Herck, Anke; Sacreas, Annelore; Beeckmans, Hanne; Vanstapel, Arno; Verleden, Stijn E.; Van Raemdonck, Dirk E.; Verleden, Geert; Vanaudenaerde, Bart M.; et al. (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSC) are a heterogeneous group of immune cells from the myeloid lineage. MDSCs expand in pathological situations, such as chronic infection, cancer, autoimmunity and allograft rejection. As chronic lung allograft dysfunction (CLAD) limits long-term survival after lung transplantation (LTx), MDSCs may play a role in its pathophysiology. We assessed phenotype and frequency of MDSCs in peripheral blood from lung transplant recipients and its relationship to post-transplant complications and immunosuppression. Granulocytic (G)-MDSC were identified and quantified by flow cytometry of blood from 4 control subjects and 20 lung transplant patients (stable n=6, infection n=5; CLAD n=9). G-MDSC functionality was assessed in vitro by their capability to block CD4 and CD8 T cell proliferation. More G-MDSC could be assessed using EDTA tubes compared to heparin tubes (p=0.004). G-MDSC were increased in stable lung transplant recipients versus non-transplant controls (52.1% versus 9.4%; p=0.0095). The infection or CLAD groups had lower G-MDSCs versus stable recipients (28.2%; p=0.041 and 33.0%; p=0.088, respectively), but were not different among CLAD phenotypes. G-MDSC tended to correlate with cyclosporine A and tacrolimus levels (r²=0.18; r²=0.17). CD4 and CD8 cells proliferation decreased by 50% and 80% if co-cultured with MDSCs (1:6 and 1:2 MDSC:T-cell ratio, respectively). In conclusion, circulating MDSCs are measurable, functional and have a G-MDSC phenotype in lung transplant patients. Their frequency is increased in stable patients, decreased during post-transplant complications, and related to level of immunosuppression. This study may pave the way for further investigations of MDSC in the context of lung transplantation.